The Universality Of Hadd Punishment With Special Reference To Piracy And Hirabah - Hendun Abd. Rahman Shah; Suraiya Osman (Universiti Sains Islam Malaysia, 2024)
Since time immemorial, piracy has become a major threat to the safety and security at sea. It has been conferred universal jurisdiction because it is considered as an enemy of humankind. Nevertheless, the punishment of this offence in international law varies from one county to another. For example in Malaysia the criminal would be punished under the Penal Code of Malaysia. On the other hand, in Islamic law the similar act of piracy or hirabah is punishable under the hadd punishment. This paper attempts to analyse the universality of the hadd punishment by making a comparison between the concept and punishments of piracy and hirabah. It is suggested that the hadd punishment for the offence of hirabah has universal character and is not changeable regardless of the place and time as compared to piracy in international law.